Metallo-surfactant complex-assisted biomimetic synthesis of silver nanoparticles: exploring relativistic effects in catalytic and sensing applications - Nagaraj, Karuppiah; Velmurugan, Gunasekaran; Thangamuniyandi, Pilavadi; Govindasamy, Chandramohan; Kamalesu, Subramaniam; Vasava, Mahesh; Prajapathi, Prajesh; Kaliyaperumal, Raja; Vaishnavi, Ellappan (ChemistrySelect, 2024)
A biological reduction method for silver nanoparticles was employed using Cassia alata extract from plant leaves, which functions as a reducing agent and the metallo-surfactant [Co(dqn)2(C12H27N)2]3+ (dqn = dipyrido[3,2-f:2′,3′-h]-quinoxaline; C12H27N)2 = dodecylamine) acting as both stabilizing and capping agent. The ratio of Ag nanoparticles (AgNPs) formation was adjusted to be equal to the amount of AgNO3, along with variations in the amount of plant leaf extract, the metallo-surfactant, pH, surrounding temperature, and the length of interaction periods. High-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), energy-dispersive spectroscopy (EDS), and energy-dispersive X-ray analysis (EDAX) were used to confirm the formation of AgNPs. The infrared results indicate the presence of hydroxyl, amine, and carboxylate groups in the extract plays a crucial role in the reduction process. Additionally, the metallo-surfactant acts as a capping agent for the silver nanoparticles, preventing agglomeration. By adjusting the acidity of the solution and the quantity of the additive metallo-surface active agent utilized, the size of AgNPs can be precisely regulated. The relativistic effects observed in this metallo-surfactant-assisted silver nanoparticle demonstrate excellent reduction capabilities for nitro compounds, effective dye degradation, and mercury sensing applications.
Online verfügbar: 05. November 2024
Gesehen am 11.07.2025